Penilaian Kesehatan Bank Syariah di Indonesia dengan Metode RGEC - Selfi Afriani Gultom; Saparuddin Siregar (ITB AAS INDONESIA Surakarta, 2022)
This study aims to determine the existence of Islamic banking health in Indonesia during 2014-2018 using the RGEC (Risk profile, Good Corporate Governance, Earning, Capital) method. Risk profile with NPF and FDR approach. GCG with 11 management elements. Income with ROA, ROE and BOPO approaches. Capital with CAR approach. The sample taken is 11 Islamic banks that have spin of (separately) from their parent, and successively submit financial reports, GCG reports and risk management reports annually to Bank Indonesia. Data collection was carried out by accessing Islamic bank data which were examined through the official websites of BI, OJK and each Islamic bank website. Data analysis used quantitative descriptive method. The results show that the average condition of Islamic banking during 2014-2018 shows a composite rating of 2 or in a healthy condition but has not reached composite 3. An important research implication for Islamic bank management is that Islamic banks must continue to increase capital and profits then manage risk and run good governance so that the health of the bank is maintained and able to compete with conventional banks.